Reprogramming of glycolysis by chemical carcinogens during tumor development. (December 2022) - D'Souza, Leonard Clinton; Shekher, Anusmita; Challagundla, Kishore B.; Sharma, Anurag; Gupta, Subash Chandra
Abstract: Indiscriminate usage and mismanagement of chemicals in the agricultural and industrial sectors have contaminated different environmental compartments. Exposure to these persistent and hazardous pollutants like heavy metals, endocrine disruptors, aromatic hydrocarbons, and pesticides can result in various health adversities, including cancer. Chemical carcinogens follow a similar pattern of carcinogenesis, like oxidative stress, chromosomal aberration, DNA double-strand break, mismatch repair, and misregulation of oncogenic and/or tumor suppressors. Out of several cancer-associated endpoints, cellular metabolic homeostasis is the commonest to be deregulated upon chemical exposure. Chemical carcinogens hamper glycolytic reprogramming to fuel the malignant transformation of the cells and/or promote cancer progression. Several regulators like Akt, ERK, Ras, c-Myc, HIF-1α, and p53 regulate glycolysis in chemical-induced carcinogenesis. However, the deregulation of the anabolic biochemistry of glucose during chemical-induced carcinogenesis remains to be uncovered. This review comprehensively covers the environmental chemical-induced glycolytic shift during carcinogenesis and its mechanism. The focus is also to fill the major gaps associated with understanding the fairy tale between environmental carcinogens and metabolic reprogramming. Although evidence from studies regarding glycolytic reprogramming in chemical carcinogenesis provides valuable insights into cancer therapy, exposure to a mixture of toxicants and their mechanism of inducing carcinogenesis still needs to be studied.